Global regularity of the 2D liquid crystal equations with weak velocity dissipation. (1st September 2017) - Yu, Yanghai; Wu, Xing; Tang, Yanbin
Abstract: In this paper we consider an initial value problem for the two-dimensional liquid crystal equations. We establish the global regularity of solutions to the equations with a weak velocity dissipation and obtain the global smooth solutions to the 2D liquid crystal equations with damping for small initial data.